Weld Defects Automatic Visual Recognition by Combined Application of Canny Edge Detector and Interval Fusion with Preference Aggregation; Information, Control, and Communication Technologies (ICCT) - Muravyov (Murav’ev) S. V. Sergey Vasilyevich (2022, 2022)
Title screen